Battling the unknown: Using composite vignettes to portray lived experiences of COVID-19 and long-COVID - Rachel Knight (PLOS ONE)
Understanding the day-to-day lived experiences of individuals who have had or are still recovering from Coronavirus Disease-19 (COVID-19), whilst a complex challenge, presents the opportunity to listen and learn. Composite vignettes provide a novel approach to explore and present descriptive portrayals of the most commonly derived experiences and recovery journeys. The thematic analysis of 47 shared accounts (semi-structured interviews with adults aged ≥18 years; 40 females; 6-11 months post-COVID-19 infection) produced a series of four intricate character stories written through the lens of a single individual. Each vignette gives a voice to and captures a different experience trajectory. From the point of initial symptom development onwards, the vignettes depict how COVID-19 has affected everyday lives, focusing on the secondary non-biological socio-psychological effects and implications. The vignettes highlight in participants’ own words: i) the potential negative implications of not addressing the psychological effects of COVID-19; ii) the lack of symptom and recovery linearity; iii) the ongoing ‘lottery’ of access to healthcare services; and iv) the highly variable, yet generally devastating, impacts that COVID-19 and consequent long-COVID has had across multiple facets of daily living.